Adsorption and dissociation of H2 on B12C6N6 cage. (14th December 2015) - Jin, Xueling; Yang, Huihui; Zhang, Yan; Chen, Hongshan
Abstract: B12 C6 N6 is an electron deficient fullerene. This paper investigates hydrogen adsorption and dissociation on two lowest energy isomers of this cluster. The results show that the adsorption of H2 molecule on the cage surface is weak physical adsorption; the adsorption energies are about 0.03 eV. The stable dissociation products are determined and the dissociation processes are traced. Molecular orbital compositions show that strong orbital interaction between the hydrogen and the cluster occurs in the process of dissociation and H2 molecule can be easily dissociated on B12 C6 N6 . We present four dissociation paths. The lowest energy barrier is only 0.35 eV, which means the dissociation can take place at moderate temperatures. Graphical abstract: Highlights: B12 C6 N6 is an electron deficient fullerene. H2 adsorption and dissociation on the low energy isomers is studied. Molecular adsorption is weak physical adsorption. H2 can be dissociated easily with an energy barrier of 0.35 eV.